Trauma systems and their role in enhancing road safety in Qatar - Hassan Al Thani (19774590) (2015)
Trauma systems have been shown to improve outcomes for trauma victims with severe and multiple complex injuries in many Western settings. This same effect have not been adequately demonstrated in rapidly developing economies nor specifically for patients with road traffic injuries [RTI's]. This session will present temporal trends in the development of the trauma system and their effect on RTI patient outcomes in Qatar. A review of each of the components of the trauma system, from pre-hospital services, emergency room care, ICU indicators, quality improvement programs, trauma registry, continuing staff education, clinical research, injury prevention and rehabilitation and their measureable impact in RTI’s will be presented and recommendations will be made for the next steps in the continued development of a national trauma system for Qatar. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.70